An Overview of Qur’ānic Studies in the West: Themes, Approaches and Methodologies (Al-Qamar, 2021)
The Quran, being foremost religious and sacred book of the Muslims, gained a significant place in the western religious studies since long. From medieval polemical refutation to the contemporary academic studies a significant number of anthological works have been produced by the western scholarship in the Qur’anic studies.  A variety of approaches and methodologies have been applied to expound multiple Qur’ānic themes which intermittently resonate among western scholars of Islam. This paper mentions a brief overview of western contribution from medieval to contemporary times and highlights the major themes in the field of western Qur’anic studies. The gradual development in applying the various socio-religious methodologies is cited as well.
Keywords: Qur’ānic Studies; Orientalism; Qur’ānic Translations; Tafsīr; Islam and West